2020
DOI: 10.3390/su12104100
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of the Relative Impacts of Land Use and Climate Change on the Key Ecosystem Services in the Hengduan Mountain Region, China

Abstract: In the Hengduan Mountain region, soil erosion is the most serious ecological environmental problem. Understanding the impact mechanism of water yield and soil erosion is essential to optimize ecosystem management and improve ecosystem services. This study used the Integrated Valuation of Ecosystem Services and Tradeoffs (InVEST) and Revised Universal Soil Loss Equation (RUSLE) models to separate the relative contributions of land use and climate change to water yield and soil erosion. The results revealed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 52 publications
2
11
1
Order By: Relevance
“…The scenario that investigated the effect of LUC change (without climate data) revealed that water yield increased by 31%, but it was not significant compared to the scenario for climate data. A similar study conducted by Dai et al ( 2020 ), shows that water yield contributed by land use and climate variability increased by 26.94% and 73.06%, respectively. Therefore, the study shows that climate variability was the main driving force for the spatial and temporal changes in water yield in the study area.…”
Section: Resultssupporting
confidence: 72%
“…The scenario that investigated the effect of LUC change (without climate data) revealed that water yield increased by 31%, but it was not significant compared to the scenario for climate data. A similar study conducted by Dai et al ( 2020 ), shows that water yield contributed by land use and climate variability increased by 26.94% and 73.06%, respectively. Therefore, the study shows that climate variability was the main driving force for the spatial and temporal changes in water yield in the study area.…”
Section: Resultssupporting
confidence: 72%
“…Soil erosion, by water and wind, is among the most serious threats to preserve soil and water resources at any spatial and temporal scale [10,11]. The expansion of agriculture and livestock farming has resulted in a significant increment of soil erosion rates that explain the development of erosional landscapes and sedimentary structures (recent alluvial plains, alluvial fans, deltas, and flat valleys infilled of sediment) in many countries, such as in Spain [12].…”
Section: Of 16mentioning
confidence: 99%
“…The precipitation erosivity in 2050 was significantly greater than that in 2020. Therefore, soil erosion is closely related to precipitation intensity [ 22 , 32 , 33 ]; that is, future climate change is more conducive to the occurrence of soil erosion [ 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…The most important problem in the Hengduan Mountain region is serious soil erosion, but with the implementation of the Yangtze River Shelter Forest Project, Natural Forest Protection Project, and Grain for Green Program, soil erosion has been well restrained [ 22 ]. However, consistent with the conclusions of many studies, this study found that there was an obvious trade-off between soil erosion and water yield; that is, regional soil erosion was reduced at the expense of water yield [ 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation